A Review of Optimisation of Search Engine using Sequential Pattern Mining Technique - Dhull, Vandana; Khurana, Shipra (International Journal of Computer Sciences and Engineering, 2014)
With the large increase in the amount of information available online, rich web data can be obtained on the internet, such as over one trillion. Web mining techniques has emerged as an important research area to help web users find their information need. Web user express their information need as queries, and expect to obtain the needed information from the web data through web mining technique. Nowadays, providing an amount of relevant web pages based on users query words is a not a big problem in search engines. Instead, the problem is that a search engine returns too many web pages, and users have to spend much time on finding their desired information from this long search result list, named as Information Overloaded Problem. Finally, search result list is re-ranked by modifying the page rank algorithm using the weights assigned to sequential patterns resulting in reduction of users navigation time within the search result